Immunological Effects of Recombinant Lactobacillus casei Expressing IHNV G Protein and Rainbow Trout (Oncorhynchus mykiss) Chemokine CK6 as an Oral Vaccine - Sun, Jinhui; Zhang, Mengmeng; Zhao, Dandan; Yang, Jiawei; Shi, Yanxue; Xu, Baoxing; Liu, Xuefei; Guan, Xueting; Shi, Wen; Liu, Min (Frontiers in Immunology, 2022)
IHNV is a virus that infects salmonids and causes serious economic damage to the salmonid farming industry. There is no specific treatment for the disease caused by this pathogen and the main preventive measure is vaccination, but this is only possible for small groups of individuals. Therefore, it is important to investigate new oral vaccines to prevent IHNV. In this study, the CK6 chemokine protein of rainbow trout and the truncated G protein of IHNV were used to construct a secretory expression recombinant L.casei vaccine for rainbow trout. The results showed that the levels of IgM and IgT antibodies in rainbow trout reached the highest level on the 15th day after the secondary immunization, and the antibodies exhibited high inhibitory activity against viral infection. Furthermore, the expression of relevant cytokines in different tissues was detected and found to be significantly higher in the oral vaccine group than in the control group. It was also found that pPG-612-CK6-G/L.casei 393 could stimulate splenic lymphocyte proliferation and improve mucosal immunity with significant differences between the immunized and control groups. When infected with IHNV, the protection rate of pPG-612-CK6-G/L.casei 393 was 66.67% higher than that of the control group. We found that pPG-612-CK6-G/L.casei 393 expressed and secreted the rainbow trout chemokine CK6 protein and IHNV truncated G protein, retaining the original immunogenicity of rainbow trout while enhancing their survival rate. This indicates that recombinant L.casei provides a theoretical basis and rationale for the development of an oral vaccine against IHNV and has important practical implications for the protection of rainbow trout from IHNV infection.